RECONSTRUCTION OF THE REVERSE BURDEN OF PROOF MECHANISM FOR THE RECOVERY OF CORRUPT ASSETS - Ade Onny Siagian; Jaka Santosa; Charine Alya Pratiwi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Corruption is an extraordinary crime, etymologically derived from the Latin words corruptus and corruption, meaning depravity, deviation from purity, and unlawful acts for personal or other people's benefit. This study aims to analyze law enforcement mechanisms for asset recovery efforts resulting from corruption, which have historically harmed state finances. The research method used is normative juridical, focusing on literature analysis and applicable legal regulations. The results indicate that optimizing the recovery of state losses can be achieved by strengthening the system of shifting the burden of proof. Furthermore, legal instruments in Indonesia allow for asset recovery through two main channels: criminal proceedings, as stipulated in the Corruption Law, and civil proceedings. This study concludes that combining a criminal approach and the effectiveness of the reverse burden of proof is key to achieving maximum and accountable asset recovery